2009
DOI: 10.1073/pnas.0812096106
|View full text |Cite|
|
Sign up to set email alerts
|

TAp73 regulates the spindle assembly checkpoint by modulating BubR1 activity

Abstract: The role of various p73 isoforms in tumorigenesis has been controversial. However, as we have recently shown, the generation of TAp73-deficient (TAp73−/−) mice reveals that TAp73 isoforms exert tumor-suppressive functions, indicating an emerging role for Trp-73 in the maintenance of genomic stability. Unlike mice lacking all p73 isoforms, TAp73−/− mice show a high incidence of spontaneous tumors. Moreover, TAp73−/− mice are infertile and produce oocytes exhibiting spindle abnormalities. These data suggest a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
110
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 50 publications
(60 reference statements)
5
110
0
1
Order By: Relevance
“…siRNA used for TAp73 downregulation were done as previously mentioned. 20 TGF-β1 treatment. Cells were incubated for 12 or 24 h with various concentrations (0, 1 or 5.0 ng/ml) of mouse TGF-β1 (mTGF-β1; Cell Signaling Technology, Beverly, MA, USA) before being continually cultured for different time periods in growth medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…siRNA used for TAp73 downregulation were done as previously mentioned. 20 TGF-β1 treatment. Cells were incubated for 12 or 24 h with various concentrations (0, 1 or 5.0 ng/ml) of mouse TGF-β1 (mTGF-β1; Cell Signaling Technology, Beverly, MA, USA) before being continually cultured for different time periods in growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that loss of the full p73 isoform TAp73 (transcriptionally active p73), containing the transactivation domain similar to p53, induced spontaneous tumor development because of enhanced genomic instability. 19,20 Interestingly, such genomic instability with loss of the spindle assembly checkpoint, was also reported in PDA where it was found associated with p73 inhibition. 21 Moreover, although mutations in TP73 are less frequent in human cancers than those of TP53, genetic aberrations of TP73 were reported in pancreatic cancer and correlated with patient outcome.…”
mentioning
confidence: 92%
“…These include, but are not limited to, the activation of the DNA damage-responsive protease caspase-2, 114 of the tumor suppressor TP53 109,115 and of other members of the TP53 family, including the TP73 variant TAp73. 116,117 In view of recent results from several laboratories indicating that mitotic aberrations can induce cell senescence, [118][119][120] and that cell death can be either apoptotic or necrotic, 8 we have recently proposed a novel definition and categorization of mitotic catastrophe based on purely functional considerations. 108 Thus, mitotic catastrophe would not constitute a 'pure' cell death executioner pathway, but an oncosuppressive mechanism that: (i) is initiated by perturbations of the mitotic apparatus (i.e., chromosomes and the complex Figure 3 Regulated necrosis.…”
Section: Definition Of 'Mitotic Catastrophe'mentioning
confidence: 99%
“…[1][2][3] Whereas p53 is a tumor suppressor and often either deleted or mutated in tumors, p73 is rarely mutated; however, its expression is often deregulated in cancer. 4,5 In p73-deficient mice, unlike in p53-deficient mice, no increase in spontaneous tumorigenesis is observed. 6 It has been demonstrated, however, that p73, in the absence of DNA damage, has a role in neuronal differentiation and development.…”
mentioning
confidence: 99%